Exploring the complexity of the childhood trait–psychopathology association: Continuity, pathoplasty, and complication effects. (28th April 2015) - De Bolle, Marleen; De Clercq, Barbara; De Caluwé, Elien; Verbeke, Lize
Abstract: Four different models have been generally proposed as plausible etiological explanations for the relation between personality and psychopathology, namely, the vulnerability, complication, pathoplasty, and spectrum or continuity model. The current study entails a joint investigation of the continuity, pathoplasty, and complication models to explain the nature of the associations between early maladaptive traits and psychopathology over time in 717 referred and community children (54.4% girls), aged from 8 to 14 years. Across a 2-year time span, maladaptive traits and psychopathology were measured at three different time points, thereby relying on comprehensive and age-specific dimensional operationalizations of both personality symptoms and psychopathology. The results demonstrate overall compelling evidence for the continuity model, finding more focused support for pathoplasty and complication effects for particular combinations of personality symptoms and psychopathology dimensions. As expected, the continuity associations were found to be more robust for those personality–psychopathology associations that are conceptually closer, such as the emotional instability/introversion–internalizing problems association and the disagreeableness–externalizing problems association. Continuity associations were also stronger when personality was considered from a maladaptive rather than from a general trait perspective. The implication of the findings for the treatment of psychopathology and personality symptoms are briefly discussed.